2017
DOI: 10.3390/en10111901
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Optimization Method for Vortex-Induced Vibration Reducing and Performance Improving in a Large Francis Turbine

Abstract: Abstract:In this paper, a new methodology is proposed to reduce the vortex-induced vibration (VIV) and improve the performance of the stay vane in a 200-MW Francis turbine. The process can be divided into two parts. Firstly, a diagnosis method for stay vane vibration based on field experiments and a finite element method (FEM) is presented. It is found that the resonance between the Kármán vortex and the stay vane is the main cause for the undesired vibration. Then, we focus on establishing an intelligent opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…9 demonstrated that the cross-sectional shape of a trailing edge has a significant effect on vortex shedding. Same conclusion can be found in the studies of Donaldson, 11 Do et al., 12 Peng et al., 13 and Wang et al. 14 Do et al.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…9 demonstrated that the cross-sectional shape of a trailing edge has a significant effect on vortex shedding. Same conclusion can be found in the studies of Donaldson, 11 Do et al., 12 Peng et al., 13 and Wang et al. 14 Do et al.…”
Section: Introductionsupporting
confidence: 81%
“…Lee et al 9 demonstrated that the cross-sectional shape of a trailing edge has a significant effect on vortex shedding. Same conclusion can be found in the studies of Donaldson, 11 Do et al, 12 Peng et al, 13 and Wang et al 14 Do et al 12 studied the flow past a blunt-edged two-dimensional NACA 0015 section with various base cavity shapes and sizes at high Reynolds numbers. The numerical prediction showed that the presence of a base cavity at the trailing edge of NACA0015 does not change the inherent Strouhal number of the 2 D section examined.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…As more sophisticated turbulence models for numerical calculation of this phenomenon are required, and more complex meshes are necessary, the number of relevant publications is relatively tiny. Mostly, it is experimental investigations that provide a basis for the validation, such as [6] of 2019, or singular analysis of individual components, see [7] in 2017, without investigating the effects on the entire unit.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the WGCL optimization problem has multiple objective functions and constraints, referred to as a multi-objective WGCL (MOWGCL) problem. Previous researchers have applied the heuristic optimization algorithms to the flow channel design and parameter optimization of hydraulic equipment [14][15][16], and several optimization studies have examined the MOWGCL problem [17][18]. However, previous studies usually converted the multi-objective optimization problem (MOOP) into one or two objective functions by setting weighting coefficients, which has intense subjectivity in optimization.…”
Section: Introductionmentioning
confidence: 99%